KUPU-KUPU DALAM KARYA TAPESTRIJANUARTI TIARA PUTRI - JANUARTI TIARA PUTRI, Drs. Erwin A, M.Sn., Drs. Efrizal, M.Pd. (Universitas Negeri Padang, 2017)
The final work entitled “ butterflies in tapestry “ this is an expression of pleasure, admiration, and concern the author of the butterfly. The form of blend of colors, motifs, gestures, and the process of life is amazing, while the enviroment is worrying, the longer the extinct. These two reasons serve as the basis for making works. Through five process strages of work, among others, preparation with passing observation, elaboration by analyzing the problem the set the main idea, synthesis matches theme subject, actual concept of making skether, preparation of tools and materials, move the sketch, the process of making works, and finishing.Keywords: Butterfly, Tapestry